The Influence of Chatbot Based Intelligence Artificial to Satisfaction Customers on E-commerce Platform - Magfiroh, Diana (Hospitality Management and Operations Journal, 2024)
Industry hospitality , especially in five- star hotels , is facing challenge big in maintain performance optimal operational environment . work and satisfaction employee known as factor important that influences productivity and quality service in sector This . However , there is gap study about influence combination second variable This to performance hotel operations . Research This aiming For analyze influence environment work and satisfaction employee to performance operations in five star hotels . Research use approach quantitative with method survey , collecting data from hotel employees who fulfill criteria certain . Sample chosen use purposive sampling technique , and the data was analyzed through regression multiple For know influence significant of each variable . Instrument study in the form of questionnaire with Likert scale is used For measure level satisfaction employees , conditions environment work , and performance operational . Research results show that environment conducive work and level? satisfaction high employee? in a way significant contribute to the improvement performance five star hotel operations . Environment supportive work and high satisfaction?? capable increase productivity employee up to 58%, indicating that both of them own great influence? to performance operational . Findings This expected can become base for hotel management in devise a strategy for create environment supportive work? as well as increase satisfaction employee use reach performance optimal operations .